Relevance of forage fish in the diet of Magellanic penguins breeding in northern Patagonia, Argentina. Issue 6 (3rd July 2017) - Yorio, Pablo; González-Zevallos, Diego; Gatto, Alejandro; Biagioni, Oscar; Castillo, Joanna
ABSTRACT: We quantified the trophic niche of Magellanic penguins ( Spheniscus magellanicus ) breeding and moulting in Golfo San Jorge, Argentina, through conventional stomach content and stable isotope analysis. A total of 112 adults were flushed during the early and late chick stages of 2011 and 2012 at Isla Vernacci Norte, and at least 15 prey taxa were found, including fishes, cephalopods, crustaceans and polychaetes. Overall, Argentine anchovy ( Engraulis anchoita ) showed the highest contribution in terms of importance by mass (68.1–85.3%, depending on chick stage and year), except for the old chick stage in 2011 when the shortfin squid ( Illex argentinus ) was the main prey consumed (56.0%). Based on carbon and nitrogen isotopic values from a total of 256 blood samples, corresponding to young and old chicks and to adults of both sexes sampled throughout the incubation, chick and moult stages at the above mentioned colony and years, Bayesian mixing model outputs showed that Argentine anchovy was always the main prey (48–86%). Bayesian mixing model outputs obtained from adults of both sexes and their chicks during the late chick stage of 2013 at Isla Vernacci Norte, Isla Tova and Isla Leones also showed that Argentine anchovy was the main prey consumed. This is the first comprehensive assessment of Magellanic penguin diet composition in northern Patagonia, quantifying the relative contribution of prey in the diet of adults and chicks at different stages of the annual cycle and years, and confirms the relevance of a forage fish such as the Argentine anchovy in its trophic ecology.